Exploring oil price exchange rate nexus for Nigeria - Zahid Muhammad; Hassan Suleiman; Reza Kouhy (FIW - Research Centre International Economics, 2011)
This paper investigates the oil price - exchange rate nexus for Nigeria during the period 2007-2010 using daily data. The generalised autoregressive conditional heteroscedasticity (GARCH) and exponential GARCH (EGARCH) models are employed to examine the impact of oil price changes on the nominal exchange rate .The outcome of this research indicates that a rise in oil prices leads to a depreciation of the Nigerian Naira vis-à-vis the US dollar over the study period.
Keywords: F31; E44; 330; Exchange rate; oil price; Nigeria; GARCH/EGARCH